Variables asociadas a la resiliencia en pacientes oncológicos atendidos en el Hospital Regional de Loreto Iquitos 2023 - Bastos Pizarro, Nelly Susana (2024)
The objective of the study was to determine the variables associated with resilience in oncological patients treated at the Regional Hospital of Loreto Iquitos 2023. The method was quantitative with a non-experimental, descriptive, correlational, cross-sectional design. The population was made up of 220 people with oncological disease treated in the oncology service of the Regional Hospital of Loreto and the sample was 140, determined through the finite population formula. The technique was the survey and the instruments were the demographic, social and clinical-pathological data sheet of the oncological patient and the Resilience Scale of the Oncological patient. SPSS statistical software version 24 was used to process the data and the nonparametric Chi Square (x2) inferential statistical test was used for correlation analysis. The results were: 35.7% were between 35 and 49 years old; 52.1% were male; 28% had a university degree; 30.7% had a dependent occupation; 23.6% were divorced; Colon cancer predominated in 37.1%; 27.9% had illness duration of 7 to 11 months; 56.4% presented a level of resilience between moderate and high, 43.6% presented a low level of resilience; finding a statistical association between the low level of resilience with age (p = 0.000), male sex (p = 0.001), level of primary education (p = 0.000), no occupation (p = 0.000), marital status (p = 0.000 ) and the duration of illness from 3 to 6 months (p= 0.000); No association was found between duration of illness and type of oncological disease (p= 0.058). Conclusion, there is a statistically significant association between demographic, social, and clinical variables and resilience in oncological patients treated at the Loreto Regional Hospital.